TRMA syndrome with a severe phenotype, cerebral infarction, and novel compound heterozygous SLC19A2 mutation: a case report - Xin Li; Qing Cheng; Yu Ding; Qun Li; Ruen Yao; Jian Wang; Xiumin Wang (BMC, 2019)
Abstract Background Thiamine-responsive megaloblastic anemia (TRMA) is a rare autosomal recessive inherited disease characterized by the clinical triad of megaloblastic anemia, sensorineural deafness, and diabetes mellitus. To date, only 100 cases of TRMA have been reported in the world. Case presentation Here, we describe a six-year-old boy with diabetes mellitus, anemia, and deafness. Additionally, he presented with thrombocytopenia, leukopenia, horizontal nystagmus, hepatomegaly, short stature, ventricular premature beat (VPB), and cerebral infarction. DNA sequencing revealed a novel compound heterozygous mutation in the SLC19A2 gene: (1) a duplication c.405dupA, p.Ala136Serfs*3 (heterozygous) and (2) a nucleotide deletion c.903delG p.Trp301Cysfs*13 (heterozygous). The patient was diagnosed with a typical TRMA. Conclusion Novel mutations in the SLC19A2 gene have been identified, expanding the mutation spectrum of the SLC19A2 gene. For the first time, VPB and cerebral infarction have been identified in patients with TRMA syndrome, providing a new understanding of the phenotype.